2022
DOI: 10.3389/fmed.2022.989405
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing DLL3 inhibition: From old promises to new therapeutic horizons

Abstract: Small-cell lung cancer (SCLC) is an aggressive neuroendocrine tumor with a high relapse rate, limited therapeutic options, and poor prognosis. The combination of chemotherapy and immune-checkpoint inhibitors brings a new therapeutic era, although the lack of predictive biomarkers of response reduces the efficacy of applying the treatment to the entire population of patients with SCLC. The lack of treatments able to bind to a specific target has always been a substantial difference to the non-small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, DLL3 can be used as a target for antitumor drugs. 34 In previous clinical studies, the antibody-drug conjugate ROVA-T was evaluated. 35,36 Despite of the negative results of these studies, extensive further research has been undertaken to develop novel targeted therapies, for example CAR-T cells against DLL3, 37 photo-, 38 and radioimmunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, DLL3 can be used as a target for antitumor drugs. 34 In previous clinical studies, the antibody-drug conjugate ROVA-T was evaluated. 35,36 Despite of the negative results of these studies, extensive further research has been undertaken to develop novel targeted therapies, for example CAR-T cells against DLL3, 37 photo-, 38 and radioimmunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…DLL3 is part of the NOTCH signaling pathway and is an optimal CTC biomarker as it is not expressed in normal lung tissue. Furthermore, DLL3 can be used as a target for antitumor drugs 34 . In previous clinical studies, the antibody‐drug conjugate ROVA‐T was evaluated 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…DLL3 is a ligand of the Notch signalling pathway, and is expressed in over 80% of SCLC surfaces, while being minimally expressed on healthy lung tissues. 27 Nuclear expression of Snail occurs in 31% of SCLC, which represents the highest of all lung cancer subtypes. 28 Furuta et al demonstrated DLL3 to be an in vitro inducer of Snail expression in SCLC.…”
Section: Dll3 Is a Key Orchestrator Of Sclc Invasion And Migration Th...mentioning
confidence: 99%
“…Targeted therapy involves developing drugs that inhibit cancer proliferation, promote cell cycle regulation, induce apoptosis or autophagy, or deliver harmful substances only to cancer cells to eliminate them [72]. Oral small-molecule drugs or monoclonal antibodies are used in targeted cancer therapy [73,74]. This treatment can improve overall survival and progression-free survival.…”
Section: Targeted Therapymentioning
confidence: 99%